Correction: Stante et al. Four Novel Caudoviricetes Bacteriophages Isolated from Baltic Sea Water Infect Colonizers of Aurelia aurita. Viruses 2023, 15, 1525 - Melissa Stante; Nancy Weiland-Bräuer; Urska Repnik; Almut Werner; Marc Bramkamp; Cynthia M. Chibani; Ruth A. Schmitz (Viruses)
In the original publication [...]